2007
DOI: 10.1038/nature06402
|View full text |Cite
|
Sign up to set email alerts
|

Optical rogue waves

Abstract: Recent observations show that the probability of encountering an extremely large rogue wave in the open ocean is much larger than expected from ordinary wave-amplitude statistics. Although considerable effort has been directed towards understanding the physics behind these mysterious and potentially destructive events, the complete picture remains uncertain. Furthermore, rogue waves have not yet been observed in other physical systems. Here, we introduce the concept of optical rogue waves, a counterpart of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
1,702
1
9

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,489 publications
(1,733 citation statements)
references
References 26 publications
21
1,702
1
9
Order By: Relevance
“…Recent experiments in water waves [26], [9] and in fibre optics [31], [21], [22], [16] (see also review articles [5], [10]) have convincingly demonstrated that rogue waves are a generic physical phenomenon deserving a comprehensive investigation [27], [5]. It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments in water waves [26], [9] and in fibre optics [31], [21], [22], [16] (see also review articles [5], [10]) have convincingly demonstrated that rogue waves are a generic physical phenomenon deserving a comprehensive investigation [27], [5]. It has also been understood that rogue waves play important role in the characterization of the nonlinear stage of modulational instability [41], [17] and particularly, in the development of integrable turbulence [40], [1], [37], [33].…”
Section: Introductionmentioning
confidence: 99%
“…Since sailors are well known story makers these monster, destructive waves that were in naval folklore perhaps for thousands of years penetrated the realm of science only recently and after quantitative observations [1,2]. Since then, they seem to spring up in many other fields including optics [3][4][5][6][7], BEC and matter waves, finance, etc [8][9][10][11][12]. Unique 2 features of rogue waves, contrary to other solitary waves, are both their extreme magnitude but also their sudden appearance and disappearance.…”
Section: Ocean Rogue Waves (Rw) -Huge Solitary Waves-have For Long Trmentioning
confidence: 99%
“…This elusive freak wave caught the imagination of the broad scientific community quite recently [8][9][10][11][12][13][14][15], triggering off an upsurge in theoretical [7,[16][17][18] and experimental [5,[8][9][10][11][12][13][14][15] studies of this unique phenomenon. For identifying such extreme waves, the suggested signature of these rare events is a deviation of the probability distribution function (PDF) of the wave amplitude from its usual random Gaussian distribution (GD), by having a long-tail, indicating that the appearance of high-intensity pulses more often has much higher probability than that predicted by the GD [19].…”
Section: Introductionmentioning
confidence: 99%
“…(b) Need for a rogue wave model on a two-dimensional plane Therefore, though the well-accepted class of PB or other solutions of the generalized NLS equation could fit into the working definition of the ocean RW, saying any wave with height more than twice the nearby significant height (average height among one-third of the highest waves) could be treated as the RW [19], they perhaps, with their restricted characteristics, can explain successfully only fixed and moderately intense RW-like events on a one-dimensional line, as observed in water channels [14], optical fibres [12,15] or optical lasers [5,8], but seem to be not satisfactory for modelling the ocean surface RWs.…”
Section: Introductionmentioning
confidence: 99%